ISOLASI DAN IDENTIFIKASI BAKTERI ENDOFIT RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb.) SEBAGAI PENGHASIL SENYAWA ANTIFUNGI TERHADAP Candida albicans - Milliana, Alvi; Safitri, Wahyu (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2015)
Infectious diseases in humans by microbes in developing countries including Indonesia remains a major problem. Forty-three percent of deaths in developing countries are caused by infections. Candida is a yeast species that often cause opportunistic infections. Disease caused by Candida can affect the mouth, vagina, skin, nails, lungs, sometimes can cause septicemia, endocarditis and meningitis. Rising yeast-leavened which has resistance to antifungal compounds that exist, encourage researchers continue to discover new compounds which have antifungal properties. In addition, the side effects caused by the use of antifungal drugs, causing people still expect the natural ingredients that can be used as an alternative treatment. According to WHO, 80% of the world's population still relies on traditional medicine, including the use of drugs from plants, one of which is the use of turmeric plant (Curcuma zanthorriza). Bioactive compounds of plants that are antifungal generally are volatile oil, aldehyde and phenol compounds. The existence of endophytic microbes in plants have economic significance for the industry favorable treatment. Endophytic microbes easily grown, have a shorter life cycle than the plant and capable of producing bioactive compounds similar to the host plant. Therefore, it is necessary to study the potential of endophytic bacteria ginger rhizome (C. xanthorrhiza) as a producer of Candida albicans antifungal compounds. This study uses ginger rhizome obtained from Stone and Pasuruan. After the isolation of microbes from ginger rhizome, further purification by means of subcultures. The endophytic microbial isolates gram staining and identification of bacteria. The result is a gram-positive bacterium Actinomyces viscosus, Bacillus brevis gram-positive bacteria and gram-negative bacteria Pseudomonas stutzeri. Then do the production of antifungal metabolites produced by endophytic bacteria and C. albicans antifungal test Paper Disc Diffusion method. The result looks the inhibition zone with a diameter of 4 mm, 15 mm and 45 mm